Finding meaning in the text : translation technique and theology in the Septuagint of Amos - Glenny, W. Edward (Leiden ; Boston : Brill, 2009)
This work is a comparison of the Septuagint of Amos with its Hebrew Vorlage for the purpose of analyzing the translation technique and theology of the translator.
Introduction -- LXX-Amos : literal or free translation? -- The translation of difficult and unknown words -- Visually ambiguous phenomena -- Anti-Syrian and anti-Samaritan bias in LXX-Amos -- God in LXX-Amos -- Gentiles, eschatology, and messianism in LXX-Amos -- The translator of LXX-Amos -- Summary.
Includes bibliographical references (pages 275-284) and indexes.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Versions -- Septuagint; Bible. -- Translating; Bible. -- Translating; Bible. -- Theology; Bible. -- Criticism, Textual; Bible. -- Language, style; Bible. -- Versions -- Septuagint -- Translating -- Theology -- Criticism, Textual -- Language, style; Theology; RELIGION -- Biblical Studies -- Prophets; Electronic books